Ultrasonographic Udder Monitoring and Disease diagnosis in She-goat - Safawat, Mst Sanjida; Naher, Samsun; Sakib, Mahmudul Hasan; Hassan, Nahid; Rahim, Md Abdur; Juyena, Nasrin Sultana (Journal of the Bangladesh Agricultural University, 2024)
Ultrasonography is an effective, non-invasive technique for regular monitoring of udder health to ensure the best quality of milk. The study was conducted to measure the diameter of gland cistern before and after milking and evaluate the effect of breeds, age, and seasons on udder diseases in she-goats. The diameter was measured through ultrasonography before and after milking and retrospective data (breed, age, season) were collected from the Veterinary Teaching Hospital, Mymensingh. Variation in gland cistern diameter (mm) was significant (p<0.05), meaning that the gland cistern’s diameter changed more before and after milking. Results also revealed an insignificant (p>0.05) difference between the left and right quarter gland cistern’s diameter independent of time. This study showed that the occurrence of udder diseases was higher in the Black Bengal breed (82%) compared to Jamuna Pari (18%). Mastitis mostly occurred at the age of between 2 to 3 years old (25.7%) and at the winter season (39.8%). All age groups had an affected incidence of 1.8% for udder wounds and showed higher occurrence during the summer season (5.3%). Furthermore, this study indicated that udder edema affection is more common in the group of goats younger than two years old and during the winter season (3.5%) This study concludes that normal physiological structures i.e. udder parenchyma, gland cistern and different pathological conditions such as mastitis, fibrosis can be easily monitored through transcutaneous ultrasonography. J Bangladesh Agril Univ 22(3): 396-403, 2024